Analysis of the driving teacher education program to prospective teachers of the first batch of Tanggamus Regency - Rona Roma Dhianti; Hesti Hesti; Idawati Idawati (Universitas Ahmad Dahlan, 2021)
The purpose of this study is to analyze and describe the extent to which teacher education programs carried out by prospective teachers of class 1 of Tanggamus Regency have an impact on students at school. This study uses a qualitative conceptual method with a constructivist approach. The data used are in the form of observations and interviews with the Prospective Motivator which includes text, symbols, pictures and graphics about the situation and background of the research, especially regarding the profile and role of the Motivator teacher in the transformation process as stated in the Motivating Teacher Training Module Document. The data collection technique is done deductively. The results of this study indicate that,